Comparison of Dental Panoramic Tomography (DPT) and CBCT for Assessment of Anatomic Relationship Between Mandibular Impacted Third Molars and Inferior Alveolar Nerve - Ghani, Momina; Durrani, Zubair (Biological and Clinical Sciences Research Journal, 2025)
The inferior alveolar nerve (IAN) injury is one of the common complications of surgical extraction of impacted mandibular third molars. The third molar and IAN are very important to be evaluated on proper imaging to evaluate their relation with anatomical distribution. Objective: To determine the diagnostic accuracy of Dental Panoramic Tomography (DPT) in assessing proximity between impacted mandibular third molars and the IAN, using Cone Beam Computed Tomography (CBCT) as the gold standard. Methods: The cross-sectional study was carried out between November 2024 and April 2025 at Rehman College of Dentistry. The 107 patients aged between 20 and 35 years old had both DPT and CBCT imaging. Radiographic findings on DPT were compared to CBCT to obtain the sensitivity, specificity, and overall accuracy. Results: DPT ranged from 75.3 percent sensitivity, 64.7 percent specificity, and 71.9 percent diagnostic accuracy. CBCT was better at detecting the location of nerves, in particular lingual canal positioning. Conclusion: CBCT provides remarkably better visualization of anatomy as compared to DPT and must be considered in high-risk scenarios.